The Effect of Country of Origin and Brand Credibility on Purchase Intention of Oppo Smartphone in Indonesia - et. al., Irma Nilasari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purchase intention reflects the consumer willingness to buy a product or service as a results of their evaluation process. Scholars agreed that country of origin play the important role to motivate the potential consumer to buy a product including smartphone, especially for those who do not have sufficient knowledge about the product. On the other hand, brand credibility also play important role as a driver for purchase intention as a results of company’s marketing efforts. The present study tries to investigate the purchase intention of Oppo smartphone by considering country of origin and brand credibility as predictors. Data collected from 369 respondents had been analysed with multiple regression analysis. The present study found that both country of origin and brand credibility simultaneously and partially have significant effect on purchase intentions.